2018
DOI: 10.1007/s00018-018-2811-2
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the VRK1 chromatin kinase in the signaling responses to DNA damage: a therapeutic target?

Abstract: DNA damage causes a local distortion of chromatin that triggers the sequential processes that participate in specific DNA repair mechanisms. This initiation of the repair response requires the involvement of a protein whose activity can be regulated by histones. Kinases are candidates to regulate and coordinate the connection between a locally altered chromatin and the response initiating signals that lead to identification of the type of lesion and the sequential steps required in specific DNA damage response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 130 publications
(202 reference statements)
1
34
0
3
Order By: Relevance
“…VRK1 is discovered as an early response gene and is one of the important factors for the initiation of cell division process, reflected on its overexpression in many cancerous tissues . Recent studies have shown direct correlation of poor clinical outcomes of breast cancer patients was associated with high expression levels of VRK1 suggesting it as a promising cancer drug target . VRK1 can phosphorylate itself (auto‐phosphorylate) as well as its interacting substrate proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VRK1 is discovered as an early response gene and is one of the important factors for the initiation of cell division process, reflected on its overexpression in many cancerous tissues . Recent studies have shown direct correlation of poor clinical outcomes of breast cancer patients was associated with high expression levels of VRK1 suggesting it as a promising cancer drug target . VRK1 can phosphorylate itself (auto‐phosphorylate) as well as its interacting substrate proteins.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recent studies have shown direct correlation of poor clinical outcomes of breast cancer patients was associated with high expression levels of VRK1 17 suggesting it as a promising cancer drug target. [16][17][18][19] VRK1 can phosphorylate itself (auto-phosphorylate) as well as its interacting substrate proteins. During mitosis, VRK1 can phosphorylate (a) barrierto-autointegration factor (BAF) to regulate the morphology of nuclear envelope 20 ; (b) H3's N-terminal tail H-15 N TROSY spectra of VRK1 in free state (red) with that of VRK1 in the presence of AMP-PNP at a molar ratio of 1:5 (VRK1: AMP-PNP; blue).…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de su papel oncogénico, puede decirse también, aunque parezca contradictorio, que VRK1 es un supresor tumoral. Esto es así debido a la regulación que esta quinasa ejerce sobre p53, que contribuye, de manera indirecta, al mantenimiento de la estabilidad genómica (185).…”
Section: Implicación De Vrk1 En Cáncerunclassified
“…La radiación ionizante es una fuente conocida de estrés oxidativo que causa daño en el ADN y el olaparib, al ser un inhibidor de PARP, interfiere en la reparación de este tipo de daño. Por tanto, el daño oxidativo provocado por la combinación de ambos tratamientos conlleva la relajación local de la cromatina y la acumulación de factores de reparación en las zonas donde se ha producido la lesión, un proceso mediado por multitud de proteínas entre las que se encuentra la quinasa humana VRK1(185). En el caso de que este tipo de roturas en el ADN se produzca en células en reposo (fases G0/G1 del ciclo celular), VRK1 promueve la fosforilación y activación de la histona H2AX (85), de NBS1 (86) y de 53BP1 (101, ya que las DSBs generadas sólo se pueden reparar por unión de extremos no homólogos (NHEJ).…”
unclassified
See 1 more Smart Citation